Effects of Intradermal Capsaicin Injections in Women With Primary and Secondary Vestibulodynia [42]. (May 2015) - Brown, Candace S.; Bachmann, Gloria A.; Wan, Jim; Foster, David Charles
Abstract : INTRODUCTION: Women with primary provoked vestibulodynia experience greater experimentally induced pain than do women with secondary provoked vestibulodynia. We determined whether central sensitization is a contributing factor by measuring cutaneous response to capsaicin, controlling for ethnic differences observed with chronic pain. METHODS: Twenty-nine women with primary vestibulodynia and 28 women with secondary provoked vestibulodynia underwent intradermal injection in the forearm. Outcome measures included spontaneous pain level (0–100 numeric rating scale) and surface areas of punctate hyperalgesia (cm 2 ) and dynamic allodynia (cm 2 ). Two-way ANOVA was performed with Bonferroni correction ( P =.01). RESULTS: Women with primary provoked vestibulodynia did not experience greater spontaneous pain (82.1±9.1 compared with 84.1±9.1, P =.63), hyperalgesia (24.1±3.8 compared with 18.2±3.4, P =.28), or allodynia (8.8±1.6 compared with 6.4±1.4, P =.39) than women with secondary provoked vestibulodynia. Black women with provoked vestibulodynia reported more spontaneous pain (91.5±8.8 compared with 65.9±8.7, P =.03), hyperalgesia (25.2±3.8 compared with 14.6±2.6, P =.07), and allodynia (9.3±1.6 compared with 5.0±0.8, P =.06) than white women, though not at .01. No interaction effects were observed for spontaneous pain ( P =.30). CONCLUSION: Ethnicity but not provoked vestibulodynia subtype may affect capsaicin-induced pain. Altered pain perception in women with primary vestibulodynia may be related to mechanisms other than central sensitization. Centrally mediated C-fibers may be related to the pain intensity observed in black women with provoked vestibulodynia.